Daniel and Revelation: Blasphemy in the Cosmic Conflict - Kuryliak, Bohdan (Open theology, 2024)
Studies of blasphemy in the book of Revelation are usually discussed in isolation from the book of Daniel, which provides an incomplete picture of this topic. This article investigates the meaning of blasphemy in the books of Daniel and Revelation. We argue that these apocalyptic books often describe the actions of the forces of evil in the Cosmic Conflict as blasphemy. The human dimension of blasphemy is expressed in the actions of kings and people (Dan. 1-6; Rev. 2:9; 16:9, 11; 21), while the eschatological dimension of blasphemy is expressed in the actions of the Antichrist (Dan. 7-12; Rev. 13:1, 5, 6; 17:3). We argue that the book of Revelation repeats and furthers the theme of blasphemy articulated in the book of Daniel.